Inducible CRISPR genome editing platform in naive human embryonic stem cells reveals JARID2 function in self-renewal. Issue 5 (4th March 2018) - Ferreccio, Amy; Mathieu, Julie; Detraux, Damien; Somasundaram, Logeshwaran; Cavanaugh, Christopher; Sopher, Bryce; Fischer, Karin; Bello, Thomas; M. Hussein, Abdiasis; Levy, Shiri; Cook, Savannah; Sidhu, Sonia B.; et al.
ABSTRACT: To easily edit the genome of naïve human embryonic stem cells (hESC), we introduced a dual cassette encoding an inducible Cas9 into the AAVS1 site of naïve hESC (iCas9). The iCas9 line retained karyotypic stability, expression of pluripotency markers, differentiation potential, and stability in 5iLA and EPS pluripotency conditions. The iCas9 line induced efficient homology–directed repair (HDR) and non-homologous end joining (NHEJ) based mutations through CRISPR-Cas9 system. We utilized the iCas9 line to study the epigenetic regulator, PRC2 in early human pluripotency. The PRC2 requirement distinguishes between early pluripotency stages, however, what regulates PRC2 activity in these stages is not understood. We show reduced H3K27me3 and pluripotency markers in JARID2 2iL-I-F hESC mutants, indicating JARID2 requirement in maintenance of hESC 2iL-I-F state. These data suggest that JARID2 regulates PRC2 in 2iL-I-F state and the lack of PRC2 function in 5iLA state may be due to lack of sufficient JARID2 protein.